KOMODIFIKASI MUSEUM: MENJAWAB FENOMENA GAYA HIDUP POSTING PADA MEDIA SOSIAL - Nikmah, Farika; Ramadani Arjo, Tri; Ismanto (SNADES, 2025)
Museum commodification focuses on enhancing the museum's role as an institution preserving the nation's collective memory for economic gain, amidst shifting tastes and needs of today's society. This research was conducted at the Indonesian Music Museum, located in Malang, East Java. The research was descriptive with a qualitative approach, with data obtained from observations, interviews, and documentation. The Indonesian Music Museum has thousands of collections, and it is the only music museum in Indonesia. However, the museum's existence is not yet widely known. Its existence is eclipsed by other tourist attractions that offer an atmosphere that attracts visitors to take photos and post them on social media. Therefore, this study proposes a commodification strategy for the spatial layout and storyline. This commodification strategy can increase the attractiveness of the Indonesian Music Museum. Visitors can find a good backdrop for photos and take videos of their visiting experience. The commodification strategy can be implemented gradually/partially, but continuously/regularly by utilizing the momentum. It is implemented thematically, utilizing moments or major holidays such as National Children's Day, so that the Indonesian Music Museum can hold National Children's Day-themed activities using its collection. Provide an interesting layout along with a storyline that visitors can document to post on their social media.